A study to determine the incidence of carcinoma of the thyroid gland in patients treated for multinodular goiter - Yogish, Vikram; Teja, Challa; Grover, Himanshi (International Surgery Journal, 2019)
Background: In the population today, the presence of multi nodular goiter (MNG) is found in quite a few people and this may be due to various reasons. The patients should be thoroughly evaluated and a detailed history must be collected. Surgical treatment is offered to patients for various reasons. The objective of this research article is, to determine the incidence and the type of carcinoma of the thyroid gland in patients treated for multinodular goiter. Methods: A total of 105 patients who had multinodular goiter were studied. The study was carried out at SRM Medical College Hospital and Research Center, Kattankulathur, Tamil Nadu, India, from March 2016 to February 2019, for a period of three years. A detailed history was obtained and a thorough clinical evaluation was done. Investigations such as, complete blood count, thyroid function tests, ultrasound of the neck, and fine needle aspiration cytology were done. The patients then underwent total thyroidectomy and the operated specimens were subjected to histopathological examination (HPE). Out of the total of 105 patients that were studied, 21 patients were found to have carcinoma of the thyroid gland. The statistics were analysed using SPSS package 16.0. Results: From the results it was seen that papillary carcinoma of the thyroid gland was most commonly found in the operated specimens. The findings were compared with other studies. Conclusions: In patients with multinodulargoiter, a thorough evaluation and a detailed histopathological examination of the operated specimens must be done.